Identification of the egusi seed trait locus (eg) and its suppressor gene associated with the thin seed coat trait in watermelon - Li, Na; Zhou, Dan; Li, Nannan; Kong, Shengnan; Shang, Jianli; Zhu, Wanting; Wang, Jiming; Ma, Shuangwu (Frontiers in Plant Science, 2023)
Egusi watermelon has a unique egusi seed type, which could be useful for breeding both edible seeds and edible flesh in watermelon. However, the genetic basis of the unique egusi seed type is not clear. In the present study, we first reported that at least two genes with inhibitory epistasis were responsible for the thin seed coat (unique egusi seed type) in watermelon. Inhertance analysis of five populations, including F2, BC and BCF2, suggested that the thin seed coat trait was controlled by a suppressor gene together with the egusi seed locus (eg) in egusi watermelon. Based on high-throughput sequencing technology, two quantitative trait loci located on chromosome 1 and chromosome 6 were identified for the thin seed coat trait in watermelon. One of the loci, the eg locus on chromosome 6, was finely mapped to a genomic region of 15.7 kb, which contained only one candidate gene. Comparative transcriptome analysis highlighted differentially expressed genes involved in cellulose and lignin synthesis between watermelon genotypes varying in the thickness of the seed coat and provided several potential candidate genes for the thin seed coat trait. Taken together, our data suggest that at least two genes are complementarily involved in the thin seed coat trait and will be useful for cloning novel genes. The results presented here provide a new reference for uncovering egusi seed genetic mechanisms and valuable information for marker-assisted selection in seed coat breeding.